Research of Tooth Surface Modification Scheme of Traction Gear Under Multi-condition - Shi Xiaochun; He Weidong; Shan Lijun (Jixie chuandong)
According to the structure characteristics of heavy locomotive traction gear transmission device,the finite element parameterized model of traction gear is established containing shafting structures considering three locomotive working conditions including starting,sustain,and rapid operation. A new type of three circular arc tooth surface modification scheme with three circular arcs is designed on the basis of the different gear meshing position,load distribution and deformation characteristics of the three different conditions. By the comparison analysis and experimental verification,the tooth contact state and load distribution of the gear by using three arcs profile modification curve is better than the gear with commonly used single arc drum gear tooth modification.